POTENTIAL OF ELECTRONIC EDUCATIONAL RESOURCES IN THE FORMATION OF INFORMATION LITERACY OF STUDENTS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The article highlights the possibilities of electronic educational resources in the formation of information literacy of students and their importance at present.